A thermogenic botanical composition containing Citrus aurantifolia fruit rind and Theobroma cacao seed extracts improves body composition in overweight adults: a clinical investigation - Amulya Chadalavada; Yean Kyoung Koo; SukJin Kim; Sudipta Veeramachaneni; Guru Ramanathan; Amulya Yalamanchi (Food & Nutrition Research)
Background and objective: CL19183, or Theolim™, is a novel, proprietary combination of standardized extracts of Citrus aurantifolia fruit rind and Theobroma cacao seeds. Earlier, CL19183 supplementation demonstrated thermogenic activity and weight loss in high-fat diet-induced obese rats. This randomized, double-blind, placebo-controlled, multicenter clinical study (RCT) assessed whether CL19183 supplementation reduced body weight (BW) and improved body composition (BC) in overweight adults. Methods: The present study recruited 120 overweight male and female subjects (25–55 years) [body mass index (BMI) of 25–29.9 kg/m2] and randomly assigned to receive daily either CL19183 (450 mg; n = 60) or a matched placebo (n = 60) over 16 weeks. The primary efficacy outcome measure was BW reduction in the intention-to-treat (ITT) population. Other efficacy measures included BC using Dual-energy X-ray absorptiometry (DEXA), waist and hip circumferences, resting metabolic rate (RMR) using indirect calorimetry, serum lipid profile, and serum biomarkers utilizing enzyme-linked immunosorbent assay (ELISA). The safety parameters were performed, including complete serum biochemistry, hematology, and urine analysis. Results: Post-trial, CL19183 supplementation resulted in significant reductions in BW (4.25 ± 1.35 vs. 0.96 ± 1.18 kg; p = 0.0001; CI [confidence interval]: 1.47, 8.59) and BMI (1.57 ± 0.53 vs 0.36 ± 0.46 kg/m2, p < 0.0001; CI: 0.87, 2.11), from baseline as compared to placebo. Similarly, total body fat (4.28 ± 1.56 vs. 0.85 ± 1.06 kg; p < 0.0001; CI: 2.35, 7.79) and fat percentage (p < 0.0001) were also reduced from baseline in the CL19183 group vs. placebo. At baseline, after a single dose of CL19183 administration and after 16 weeks, RMR was significantly increased (p < 0.0001 vs. placebo). After 8 and 16 weeks of supplementation, CL19183 significantly increased serum adiponectin and glucagon-like peptide-1 and decreased ghrelin levels vs. baseline and placebo. No major adverse events were reported. Conclusion: CL19183 supplementation was well-tolerated and led to significant BW reduction and improvements in BC over 16 weeks.